Volatile organic compounds of royal jellies obtained from honeybee (Apis mellifera L.) colonies fed with different industrial sugars at different locations - Seker, Ibrahim; Karlidag, Semiramis; Akyol, Abuzer; Yil, Gulsah; Koseman, Abdurrahman; Uyumlu, Ayse Burcin; Yilmaztekin, Murat (Springer, 2025)
The aim of this study was to reveal differences in the volatile organic compounds (VOCs) of royal jellies (RJs) produced by honey bee (Apis mellifera L.) colonies fed with 3 different industrial sugars at 2 different locations. VOCs in the RJ samples were extracted via headspace-solid phase micro-extraction and analysed by gas chromatography-mass spectrometry. In total, 46 compounds, including 3 esters, 14 alcohols, 5 acids, 1 aldehyde, 14 ketones, 3 lactones, 2 terpenes and 4 other compounds, were identified in the RJ samples obtained from honeybee (Apis mellifera L.) colonies reared in Do & gbreve;an & scedil;ehir. A total of 45 compounds, including 3 esters, 14 alcohols, 5 acids, 1 aldehyde, 14 ketones, 4 lactones, 2 terpenes and 2 other compounds, were detected in the RJ samples obtained from honeybee (Apis mellifera L.) colonies reared in the Uluk & ouml;y location. It has been determined that different locations and different feeding conditions significantly affect the composition and amounts of volatile organic compounds in royal jelly.
Keywords: Royal jelly; Location; Industrial sugars; Feeding; Volatile organic compounds; GC-MS